PENENTUAN KADAR TANIN PENENTUAN KADAR TANIN PADA EKSTRAK ETANOL DAUN KARET KEBO (Ficus elastica Roxb. ex Hornem) DENGAN MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-Vis - renhoran, aulia azahra; Suhaenah, Asriani; Muflihunna, A. (PHARMACY UMI JOURNAL SYSTEM, 2024)
This research aims to determine the tannin content in the ethanol extract of kebo rubber leaves (Ficus elastica Roxb. ex Hornem). Rubber plants (Ficus elastica Roxb. ex Hornem) are plants that are widely used as traditional medicine, the leaves of this plant are used as medicine to treat diarrhea. , stops bleeding and treats hemorrhoids. Many of the benefits and properties of the kebo rubber plant (Ficus elastica Roxb. ex Hornem) cannot be separated from the compounds contained in it, such as phenolics, tannins, flavonoids and saponins. Simplicia was extracted using the maceration method with 96% concentration of ethanol solvent for 3x24 hours. Determination of tannin content using the UV-Vis spectrophotometric method, with a maximum wavelength of 772 nm, using gallic acid as a comparison. The research results showed that the total tannin content in the ethanol extract was an average of 31.708mgQE/g.